Morphological, anatomical and histological studies on knob and beak characters of six goose breeds from China - Zhang, Yang; Xu, Xinlei; Ji, Wangyang; Qi, Shangzong; Bao, Qiang; Zhang, Yong; Zhang, Yu; Xu, Qi; Chen, Guohong (Frontiers in Physiology, 2023)
The knob serves as both a sexual indicator of a goose’s maturity and a significant packaging attribute that garners consumer attention. However, studies regarding the morphological, anatomical and histological traits of different breeds and ages on the on knob in goose are lacking. In this study, six breeds with typical goose knob types were selected, and their knob size, morphological, anatomical and histological traits were characterized. The results showed that: Knob was more prominent in gander than in female goose, and the difference was the most obvious in Magang goose. Wanxi white goose and Shitou goose had the largest knob bulge, while Magang goose and Sichuan white goose were smaller. The total knob volume of Wanxi White goose and Shitou goose was significantly higher than that of other breeds, regardless of male or female (p < 0.05). The beak volume of Wanxi White goose and gander was significantly higher than that of other goose breeds (p < 0.05). Furthermore, the observation revealed that the “knob” primarily consisted of skin-derived tissue and bony protrusions. As age advances, the knob of both male and female geese undergoes synchronous development, with the knob of male geese typically surpassing that of their female counterparts during the same period. The growth rate of knob in male goose was the fastest from 70 to 120 days of age, and slowed down from 300 to 500 days of age. The growth rate of knob in female goose was slower than that in male goose. There were essential differences in the composition of Yangzhou goose knob and Magang goose knob. The subcutaneous tissue of Magang goose was rich, and the thickness of epidermis, dermis and various layers was significantly smaller than that of Yangzhou goose (p < 0.05). With the growth of goose knob, the cells of the epidermal spinous layer became denser and gradually condensed into an overall structure, and there was a clear boundary between the dermis and epidermis after adult. In adulthood, the fiber fascicle network was staggered and dense, with greater toughness and elasticity, and the stratum corneum, epidermis, reticular layer, dermis and other skin structural layers became thicker.